ANALISIS PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN, DAN NILAI PELANGGAN TERHADAP KEPUTUSAN PEMBELIAN (STUDI PADA KEDAI KOPI â€œKopiKitaKamiâ€ DI KABUPATEN TEMANGGUNG) - Ibrahim, Hudan Majid; Sudaryanto, Budi (Diponegoro Journal of Management, 2019)
Lately, coffee drinks have been favored by many in the community, which has led to a high competition for coffee shops, one of which is in Temanggung Regency. Companies must be able to compete and create new marketing strategies to survive and be able to reach a larger market share. This study aims to explain the effect of product quality, service quality and customer value in influencing purchasing decisions at KopiKitaKami coffee shops in Temanggung Regency.The sampling technique is done by accidental sampling. The number of samples as many as 130 respondents who live in Temanggung Regency and are customers who visit the KopiKitaKami coffee shop with at least one time bought at KopiKitaKami. The analytical tool used in this research is Structural Equation Modeling (SEM) with AMOS 24.0 program.The results of this study indicate that product quality and service quality have a positive effect on customer value. As well as product quality, service quality, and customer value have a positive effect on purchasing decisions.